Peningkatan Literasi Keamanan Digital melalui Edukasi Pencegahan dan Penanggulangan Serangan Phishing bagi Siswa - Melda Agnes Manuhutu; Michael Michael; Forlita Forlita; Dewi Dewi; Sisilia Sisilia; Jeniffer Jeniffer; Marvy Marvy; Sawo Sawo; Elsaday Elsaday (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
This community service activity was conducted at SD Negeri 15 Kota Sorong with the aim of providing cyber crime education focusing on phishing prevention to grade 5 elementary school students. The program was carried out through six systematic stages: preparation, socialization, training and interaction, technology application, mentoring and evaluation, and program continuity. A total of 58 students and one accompanying teacher participated in the activity. Interactive methods were employed, including presentations, storytelling, picture guessing games, simple quizzes, and direct technology demonstrations. Results showed that approximately 88% of students were able to correctly identify characteristics of phishing messages, with an average comprehension score of 85 out of 100. This activity is expected to build long-term digital safety awareness among elementary school students in Kota Sorong.